Natural inspiration technique for the parameter optimization of A-GTAW welding of naval steel. (2020) - Sathish, T.; Dinesh Kumar, S.; Muthukumar, K.; Karthick, S.
Abstract: The DMR249A steel is uniquely developed by a high strength low alloy (HSLA) steel. In India, the steel is being used for the construction of Indian Aircraft Carrier and other shipyards. Develop the depth of penetration (DOP) and achieve in a single pass for gas tungsten arc welding (GTAW) process. The GTAW process is called activated flux gas tungsten arc welding (A-GTAW). Response surface methodology (RSM) and Taguchi technique are used for Design of experiments (DOE) approach. Depth of penetration in a single pass to optimize the welding parameters. The current, torch speed and arc gap are considered as an input variable. The DOP was considered as the response variable. To develop both optimization technique depends on the process parameters. To identified optimum process parameters were validated by bead on plate experiments. The RSM (D-optimal) and Taguchi optimization technique the DOP values are measured and predicted to the RMS error. Thus, RSM (D-optimal) was observed to predict optimized welding process parameters for achieving maximum DOP with better accuracy during A-GTAW process.